Are Obstetrician-Gynecologists Satisfied with Their Maternal–Fetal Medicine Consultants? A Survey - Wenstrom, Katharine; Erickson, Kristine; Schulkin, Jay (American Journal of Perinatology, 2012)
Objective To survey generalist obstetrician-gynecologists about their satisfaction with and patterns of referral to maternal–fetal medicine (MFM) specialists.Study Design A survey was sent three times to 1030 randomly selected American Congress of Obstetricians and Gynecologists members across the country, and results were tabulated.Results A total of 516 surveys (50%) were returned; 68% of respondents were satisfied (S) with available MFM services and 31% were not satisfied (Not S). S and Not S respondents were similar with respect to age, gender, years in practice, type of practice, hours worked per week, proximity to MFM specialists, number of deliveries per year, and level of nursery in their hospital. Reasons for dissatisfaction included: MFM specialist not readily available (49%), during the day (26%), at night (35%), or on weekends (36%); MFM specialist unwilling to take care of hospitalized patients (26%); or MFM specialist does only ultrasound, chorionic villus sampling, and amniocentesis (32%). Although some generalists do not consult MFM specialists frequently, the majority of both S and Not S respondents would request an MFM consult or comanagement for 26 of 38 specific maternal, fetal, and obstetric diagnoses/complications.Conclusion The majority of obstetrician-gynecologists are satisfied with their MFM support. The dissatisfaction expressed by 31% of generalists might be ameliorated if individual MFM specialists increased their availability and/or broadened their scope of practice.
Keywords: generalist's opinion of MFM services